METODE RISK PROFILE GOOD CORPORATE GOVERNANCE EARNING DAN CAPITAL (RGEC) UNTUK MENILAI TINGKAT KESEHATAN BANK PADA PT BANK RAKYAT INDONESIA Tbk - Lizvan Mangatur Sitorus (Jurnal Ilmiah Raflesia Akuntansi, 2021)
Abstract - This study aims to assess the soundness of the bank using the Risk Profile, Good Corporate Governance, Earning and Capital (RGEC) method for the 2018-2020 period. Based on the results of research, the health level of PT Bank Rakyat Indonesia Persero (Tbk) in 2018 to 2020 received a Composite Rating 1 (PK-1) which is "Very Healthy" because the determination of the composite rating is taken based on judgment from the results of each factor, namely the Risk Profile assessed by NPL and LDR, Good Corporate Governance taken from the results of self-assessment, Earnings using ROA and NIM and Capital using CAR more get a rating of one "Very Healthy". So that the results of the composite ranking of PT Bank Rakyat Indonesia Persero (Tbk) in 2018 to 2020 get the first rank, namely with the title "Very Healthy".